1999
DOI: 10.1128/mcb.19.5.3916
|View full text |Cite
|
Sign up to set email alerts
|

Induction of p21WAF1/CIP1 and Inhibition of Cdk2 Mediated by the Tumor Suppressor p16INK4a

Abstract: The tumor suppressor p16INK4a inhibits cyclin-dependent kinases 4 and 6. This activates the retinoblastoma protein (pRB) and, through incompletely understood events, arrests the cell division cycle. To permit biochemical analysis of the arrest, we generated U2-OS osteogenic sarcoma cell clones in which p16 transcription could be induced. In these clones, binding of p16 to cdk4 and cdk6 abrogated binding of cyclin D1, p27 KIP1 , and p21 WAF1/CIP1 . Concomitantly, the total cellular level of p21 increased severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
1
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 94 publications
5
82
1
1
Order By: Relevance
“…This might be the result of a p16 indirect e ect in the activity of cyclin E and/or cyclin A, most likely as a result of releasing p27/p21 from CDK4/6 complexes. The released p27/p21 CKIs have been shown to bind CDK2 complexes and inhibit their activity (McConnell et al, 1999;Mitra et al, 1999). Altogether these results suggest that E1A modulates the phosphorylation status of p130 by blocking D-type cyclin activity and by inducing cyclin E and/or A activities.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…This might be the result of a p16 indirect e ect in the activity of cyclin E and/or cyclin A, most likely as a result of releasing p27/p21 from CDK4/6 complexes. The released p27/p21 CKIs have been shown to bind CDK2 complexes and inhibit their activity (McConnell et al, 1999;Mitra et al, 1999). Altogether these results suggest that E1A modulates the phosphorylation status of p130 by blocking D-type cyclin activity and by inducing cyclin E and/or A activities.…”
Section: Resultssupporting
confidence: 55%
“…It has also been shown that cells lacking a functional pRB express high levels of p16 (Parry et al, 1995;Serrano et al, 1993;Tam et al, 1994;Yeager et al, 1995). However, involvement of p16 in E1A-mediated e ects on phosphorylation of p130 and p107 is unlikely since E1A blocks hyperphosphorylation of both pocket proteins in U-2 OS cells (ParrenÄ o et al, 2000), which do not expres p16 (McConnell et al, 1999;Mitra et al, 1999). Thus, we asked the question of whether the E1A-mediated changes in p130 and p107 phosphorylation could be explained by changes in the expression of G1/S cyclins.…”
Section: Resultsmentioning
confidence: 99%
“…Although p19 ARF abrogates the ability of MDM2 to negatively regulate p53 activity, it has yet to be directly implicated as an RMS tumor suppressor; in fact, ARF-de®cient mice fail to develop RMS (Kamijo et al, 1999). Recently, another link between the RB and p53 pathways was forged by the ®nding that increased p16 INK4a expression induced p21 CIP1 through a post-transcriptional mechanism in osteosarcoma cells (Mitra et al, 1999). Interestingly, mice harboring a transgene encoding the SV40 T-antigen, a potent viral oncogene capable of simultaneously inactivating both p53 and pRB (reviewed by Van Dyke, 1994), develop RMS at a signi®cantly higher incidence and a much shorter latency, o ering credible evidence for the participation of both pathways in the formation of RMS (Teitz et al, 1993; Table 2).…”
Section: Digging Deeper ± Prb and P53 At The Crossroadsmentioning
confidence: 99%
“…Numerous data from the literature suggest the existence of a functional collaboration between distinct CDK inhibitor genes (Franklin et al, 2000). Indeed, it has been recently demonstrated that cell-cycle inhibition by p16 is associated with a post-transcriptional induction of p21 and a strong inhibition of cyclin E-cdk2 kinase activity (Mitra et al, 1999). Moreover, it has been shown that members of the p21 family of proteins promote the association of D-type cyclins with CDKs by counteracting the effects of p16 molecules (Parry et al, 1999).…”
Section: The Cell-cycle Machinery and Lung Cancermentioning
confidence: 99%